A systematic review and meta-analysis of postoperative intervention effects in elderly patients with gastrointestinal cancer based on the protection motivation theory - Wei, Yanhong; Zhang, Li; Wei, Zhenqi; Zheng, Li; Chai, Chen; Ding, Ye (Frontiers in Oncology, 2025)
ObjectiveThis study aims to evaluate the effect of postoperative interventions based on the Protection Motivation Theory (PMT) on postoperative recovery in elderly gastrointestinal cancer patients, providing scientific evidence to support clinical practice and improving postoperative recovery quality and survival rates in elderly patients.MethodsA systematic review and meta-analysis were conducted, with relevant studies retrieved from multiple Chinese and English databases. The studies selected met the inclusion criteria, involving elderly gastrointestinal cancer patients aged 60 years or older, and interventions guided by PMT, including health education, behavior modification, or psychological interventions. The primary outcomes assessed were postoperative complication rates, psychological stress scores, and quality of life scores.ResultsA total of 8 randomized controlled trials (RCTs) were included, with a total of 319 participants. Meta-analysis results indicated that the PMT intervention group had a significantly lower postoperative complication rate compared to the conventional health education group (MD = 1.81, 95% CI:1.30–2.53, P = 0.0005). The PMT intervention group also showed significantly lower postoperative psychological stress scores than the conventional group (MD = -15.64, 95% CI: -17.34 to -13.95, P < 0.00001). Moreover, the PMT intervention group exhibited significantly better postoperative quality of life scores compared to the conventional care group (MD=-8.99, 95% CI:-9.60 to-8.38, P < 0.00001).ConclusionPostoperative interventions based on the Protection Motivation Theory can significantly improve postoperative recovery in elderly gastrointestinal cancer patients by enhancing recovery outcomes, reducing complication rates, improving psychological stress levels, and enhancing quality of life, demonstrating strong clinical application value.